Archaeometric characterization of historical-contemporaneous marbles from Waldensian Valleys of Piedmont (Dora-Maira Massif, Cottian Alps, Italy). (October 2022) - Vola, G.; Ardit, M.; Frijia, G.; Cavallo, A.; Natali, C.; Balma Mion, C.; Lugli, F.; Primavori, P.
Graphical abstract: Highlights: In-depth archaeometric study of marbles from Waldensian valleys (Piedmont, NW Alps) Compositional and microstructural characterization of historical-contemporaneous marbles. Identification of diagnostic features for tracing marble provenance. Isotopic dataset of ancient marbles from Piedmont used in architecture and statuary. Abstract: This paper deals with mineralogical-petrographic, microstructural and geochemical analyses for the archaeometric characterization of silicate-bearing granoblastic marbles from the so-called Waldensian Valleys of Piedmont (i.e. Pellice, Germanasca and lower Chisone valleys, Cottian Alps, Italy). These stones, belonging to the Dora-Maira Massif of the Penninic domain (pre-Carboniferous), are often associated with a talc-bearing mineralization. Since the XIV century, "Waldensian" marbles have been subjected to a relatively intense extractive activity (nowadays almost completely abandoned) and have been widely used, especially during XVI-XIX century, for decoration purposes and as building materials in the Duchy of Savoy, as well as later, in Italy and abroad. Fifteen samples representing four lithofacies and commercial types (named " Statuary white ", " Bardiglio gray ", " Zebrato gray " and " Cipollino green " marbles) from four different quarries (named Cabitto, La Majera, Rocca Corba, and Caugis ), were studied through a multianalytical approach. The isotopic signature, combined with the mineral chemistry, allowed tracing marbles origin uniquely. The resulting database can be employed either in the cultural heritage, or in the conservation and restoration science, to identify each "Waldensian" marble from different decorative stones with similar microstructural and/or compositional features, but different origin.